2020
DOI: 10.1371/journal.pone.0229400
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Leishmania braziliensis antigen-specific CD4+ T, CD8+ T, NK and CD3+CD56+NKT cells in the immunopathogenesis of cutaneous leishmaniasis patients: Cytotoxic, activation and exhaustion profiles

Abstract: The pathogenesis of cutaneous leishmaniasis (CL) caused by Leishmania (Viannia) braziliensis is dictated mainly by the immune-mediated-tissue inflammation developed. The understanding of the immunological mechanisms that generate tissue damage or resolution of lesions is the key to the development of effective vaccine protocols and proper therapeutic schemes. It is clear that the specific immune response mediated by T cells is responsible for the beneficial outcome of the disease, however, the roles of CD4 + T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
1
7
0
4
Order By: Relevance
“…Some studies cited that NK cells are protective against leishmaniasis while others suggested the contrary indicating a cytotoxic role contributing to tissue damage in Lb -infection ( 24 26 ). A recent study observed increased frequency of cytotoxic NK cells in cell cultures of PBMC stimulated with Lb -antigens from patients with Lb -CL before treatment, while high frequencies of exhaustion NK cells during treatment ( 27 ). Administration of Met-RANTES (an anti-CCL5) in C57/BL6 mice render them susceptible to L. major ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies cited that NK cells are protective against leishmaniasis while others suggested the contrary indicating a cytotoxic role contributing to tissue damage in Lb -infection ( 24 26 ). A recent study observed increased frequency of cytotoxic NK cells in cell cultures of PBMC stimulated with Lb -antigens from patients with Lb -CL before treatment, while high frequencies of exhaustion NK cells during treatment ( 27 ). Administration of Met-RANTES (an anti-CCL5) in C57/BL6 mice render them susceptible to L. major ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, alguns estudos observaram o subtipo celular Th17, que produz IL-17 e aumenta a produção de IL-1, IL-6 e NOS2, agindo no auxílio dos linfócitos Th1 e Th2 quando se tem a necessidade maior de uma inflamação tecidual por patógenos resistentes a ação do Th1 e Th2 2,4,7,18 . Mas, no estudo do artigo XV, diferente das células Th17, mostrou-se que a ação das células Treg podem tornar camundongos suscetíveis à infecção ou reativar uma infecção secundária ou podem controlar as respostas imunopatológicas a depender da espécie 15 .…”
Section: Discussionunclassified
“…Todavia, estudos apontam que, dependendo da espécie do parasito e do hospedeiro, os neutrófilos podem combater ou proteger os patógenos. Os neutrófilos ao fagocitarem e se infectarem com as formas promastigotas de Leishmania são fagocitados por macrófagos, que servem como células hospedeiras na multiplicação do parasito 7,9,12 . Dessa forma.…”
Section: Principais Células E Funções Na Defesa Inataunclassified
See 2 more Smart Citations